Some Ecological Studies of Detritus as a Major Component of Lotic Ecosystem - Kumari, Rakhi (International Journal of Pharmaceutical & Biological Archive, 2024)
Introduction: Detritus, the decomposing organic matter found in lotic (flowing water) ecosystems, plays a critical role in supporting biodiversity and ecosystem function. It serves as a primary energy source for many organisms within these ecosystems, influencing nutrient cycling and food webs. This abstract summarizes recent ecological studies on the significance of detritus in lotic environments. Role of Detritus in Lotic Ecosystems: Ecologists now believe that particulate detritus is the food resource that supports, directly or indirectly, well over half the animal production in most ecosystems. Most animals wait until plants die and partly decompose before using this material food. Invertebrates such as shredders, collectors, and detritivores rely on detritus as a food source, while microorganisms decompose it into simpler compounds, contributing to nutrient cycling. Studies have shown that the quality and quantity of detritus are influenced by factors such as vegetation cover, hydrology, and land use (Wallace et al., 1997; Graça et al., 2001). This interaction supports a complex food web, with primary producers and consumers depending on the energy and nutrients released from detritus. Detritus Decomposition and Ecosystem Function: At Station 1, the minimum quantum (0.012 g/m2) of the dry detritus was recorded in August, 2022; whereas the maximum (0.363 2 g/m2) in April, 2022 during the first year. In the second year, the minimum (0.027 g/m2) was observed in September, 2023 and maximum (0.568 g/m2) during January, 2023. At Station 2, the dry detrital content was slightly higher as compared to Station 1: but the quantum of variation showed similar seasonality, at both the lolic stations, in which (0.043 g/m2) was recorded in August and highest (0.782 g/m2) in March, during the first year. In the second year the minimum detrital content (0.0:36 2 g/m2) was observed in September, 2023 and the maximum (0.331 g/m2) in January, 2023. Conclusion: Detritus is a crucial component of lotic ecosystems, influencing energy flow, nutrient dynamics, and biodiversity. Understanding its role in ecosystem processes is essential for managing freshwater habitats and mitigating the impacts of human activities on these environments.